Random Weighting Estimation of Poisson Distributions - Shesheng Gao; Wenhui Wei; Yongmin Zhong; Chengfan Gu (Institute of Advanced Engineering and Science, 2013)
This paper presents a new random weighting method for estimation of Poisson distributions. A theory is established for random weighting estimation of the population parameters of two Poisson distributions with partially missing data. The strong convergence of the random weighting estimation is rigorously proved under the condition of . The random weighting estimation of one-sided confidence intervals in Poisson distribution is also constructed, and its coverage probability is rigorously proved by using the Edgeworth expansion under certain conditions. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1891